Resistorless electronically tunable floating memtranstor emulator and its application to chaotic oscillators - Cayir, Muzaffer; Sagbas, Mehmet; Minaei, Shahram; Ayten, Umut Engin (ELSEVIER GMBH, 2025)
The Memtranstor, recognized as the fourth fundamental memory element after the memristor, memcapacitor, and meminductor, establishes a direct relationship between charge and magnetic flux via nonlinear magnetic interactions. This paper presents a novel electronically tunable and resistorless floating memtranstor emulator, along with its application in a chaotic oscillator circuit. The memtranstor circuit proposed in this paper is implemented using a voltage difference transconductance amplifier (VDTA), a dual output differential voltage current conveyor (DO-DVCC), an analog multiplier, and three grounded capacitors. The design is fully resistorless and offers electronic tunability of its characteristics. To validate the performance and functionality of the proposed circuit, extensive PSPICE simulations were conducted using 0.18 mu m CMOS technology parameters. Various simulations were performed by changing the parameters of the model, including Monte Carlo simulations and compressed hysteresis loops under different transconductance values and frequencies. A memtranstorbased chaotic oscillator is also presented as an example of application and verified through PSPICE simulations. Furthermore, experimental studies were conducted using commercially available ICs.
Keywords: Memtranstor; Chaotic oscillator; Emulator circuits; Pinched hysteresis loop; Non-ideal effects; Memory elements; CIRCUIT; Engineering; Telecommunications